Onfarm participatory evaluation of East African highland banana Matooke hybrids (Musa spp.) - Nowankunda, K.; Barekye Erima, R.; Batte, M.; Tushemereirwe, Wilberforce K.; Ssali, R.T. (2010)
The East African highland bananas ‘Matooke’ (Musa spp.) are unique interms of utilization, their taste and the cultural attachment to the people in the EastAfrica region. Research efforts have been directed towards improving these bananasfor disease resistance, pest resistance and higher yields, while keeping their uniquetaste and other culinary qualities. This paper presents results of an on-farmparticipatory evaluation study of 18 conventionally bred hybrids selected from anearly evaluation trial at the Kawanda Agricultural Research Institute. The 18‘Matooke’ hybrids (17 with AAA genome; one with AAAA genome) and a localcultivar were planted in farmers’ fields in Kasangombe sub-county, Nakasekedistrict in Central Uganda. The hybrids were evaluated for consumer acceptability,black Sigatoka resistance and agronomic performance The ‘Matooke’ hybrids ‘M2’,‘M9’, ‘M14’ and ‘M17’ (AAA genome) were selected as the most acceptable hybrids,combining high yields with resistance to black Sigatoka.